Exploring Teachers’ Creative Teaching Strategies in Teaching Arabic as a Foreign Language at a Private Islamic Secondary School in Malaysia - Faizuddin, Ahmad; An-Nuaimy, Tumin; Al-Anshory, Ahmad Suhail (IIUM Journal of Educational Studies, 2016)
Arabic is an important language for Muslims but teaching the language is not an easy task. It needs efforts to improve and simplify the learning process through creative teaching strategies. Creative teaching involves the development of materials and approaches that foster students’ interests and motivation in learning. This study explored the experiences of Arabic teachers in fostering students’ interests by developing creative approaches in teaching Arabic as a foreign language at Adni Islamic School, a private Islamic secondary school in Malaysia. In collecting the data, semi-structured interviews were used as part of qualitative research. The findings indicated that teachers have been using creative teaching strategies in the teaching and learning process. These are categorized into three strategies: (1) creativity in making daily lesson plans, (2) creativity during the teaching and learning process, and (3) creativity in evaluating and assessing the outcomes of teaching. The application of these creative strategies is in accordance with the message of the Islamic principles of teaching. Recommendations were made to the relevant authorities, including the teachers themselves, so that creative teaching can be applied to the subject of Arabic language in order to produce a meaningful lesson.